Magmatic evolution of the Kikai caldera revealed by zircon triple dating and its chemistry - Hisatoshi Ito (Scientific Reports)
Abstract Reconstructing the volcanic history of the Kikai caldera, a large active volcano that produced a ~ 160 km3 eruption at 7.3 ka off the southern coast of Kyushu Island (southwest Japan), is crucial to assess potential future volcanic hazards at both regional and global scales. However, revealing its volcanic history before the 7.3 ka eruption has been challenging due to the caldera being mostly submerged. In this study, we present evidence that the Kikai caldera erupted a geochemically distinct silicic lava at ~ 250 ka by using zircon triple (U-Pb, Th-Pb, U-Th) dating and its chemistry. The presence of 1.5–1.0 Ma zircons in the 7.3 ka eruption deposits suggests that zircon crystallization in the Kikai caldera began during this period. We further infer large eruptions occurred around 0.7–0.6 Ma, suggesting that the Kikai caldera may have experienced at least 5 major eruptions during its 1.0–1.5-million-year magmatic evolution.